The deep biology of cognition: Moving toward a comprehensive neurodevelopmental model of Turner syndrome. Issue 1 (11th February 2019) - Knickmeyer, Rebecca C.; Hooper, Stephen R.
Abstract : Individuals with Turner syndrome (TS) often exhibit specific deficits in visual–spatial functions, arithmetical abilities, social cognition, and executive functions with preserved general intelligence and preserved or enhanced verbal skills. This unique pattern of cognitive strengths and weaknesses is accompanied by a well‐described neuroanatomical phenotype characterized by decreased gray matter volumes in premotor, somatosensory, and parietal‐occipital cortex, and increased volumes of the amygdala and orbitofrontal cortex. Why the absence of the second sex chromosome should produce these effects remains poorly understood. In this article, we propose that the TS research community leverage recent advances in neuroimaging, large‐scale data‐rich biology (omics), and patient‐powered research registries to build a comprehensive neurodevelopmental model of TS.